The Economic Impact of Global Tourism: A Review of Contributions and Challenges in Developing Countries - Akpoviroro, Kowo Solomon (Politeknik Siber Cerdika Internasional, 2024)
Global tourism has been one of booster main growth economy in developing countries, which contributes significant to improvement income national, creation field work, and development infrastructure. However, this contribution is faced with various challenges, such as dependence economy, vulnerability to global crisis, and its impact environment that needs managed in a way sustainable. This study aims to analyze impact economy from sector global tourism in developing countries, with highlight its role in improving welfare economy at a time identify challenges that arise from dependence on this sector. The research method used is study library and analysis of secondary data taken from various sources source relevant international, such as report annual report from the World Tourism Organization (UNWTO) and the World Bank. The research results show that although sector tourism contributes positive to growth economy, developing countries often face limitations in optimizing profit term long consequence lack of investment sustainable, instability global economy, and the need improvement capacity management destination. This finding underlines the importance of diversification strategy economy and improvement sustainable infrastructure to mitigate risks related. The implications of this study are recommendation policies that can help developing countries to be more resilient in the face of challenges and take advantage of potential global tourism in general maximum.